2009
DOI: 10.1104/pp.109.149849
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase-Like Protein CTL1 Plays a Role in Altering Root System Architecture in Response to Multiple Environmental Conditions      

Abstract: Plant root architecture is highly responsive to changes in nutrient availability. However, the molecular mechanisms governing the adaptability of root systems to changing environmental conditions is poorly understood. A screen for abnormal root architecture responses to high nitrate in the growth medium was carried out for a population of ethyl methanesulfonatemutagenized Arabidopsis (Arabidopsis thaliana). The growth and root architecture of the arm (for anion altered root morphology) mutant described here wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 62 publications
8
79
0
Order By: Relevance
“…Asterisks indicate significant changes in percentage of colocalization compared with control treatment (Student's t test; *P < 0.05; **P < 0.01). Even though important amino acids for catalytic activity appear to have been changed in the CTLs (Passarinho and de Vries, 2002;Hermans et al, 2010;Hossain et al, 2010), it is still possible that the proteins have retained catalytic activities. However, chitinase activity of recombinant CTL1 protein purified from Escherichia coli was tested in vitro with negative results (Zhong et al, 2002;Hermans et al, 2010).…”
Section: Ctl1 and Ctl2 Bind Glucan-containing Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Asterisks indicate significant changes in percentage of colocalization compared with control treatment (Student's t test; *P < 0.05; **P < 0.01). Even though important amino acids for catalytic activity appear to have been changed in the CTLs (Passarinho and de Vries, 2002;Hermans et al, 2010;Hossain et al, 2010), it is still possible that the proteins have retained catalytic activities. However, chitinase activity of recombinant CTL1 protein purified from Escherichia coli was tested in vitro with negative results (Zhong et al, 2002;Hermans et al, 2010).…”
Section: Ctl1 and Ctl2 Bind Glucan-containing Polymersmentioning
confidence: 99%
“…However, the biological function of the CTLs remains elusive. Mutations in CTL1/POM1 cause abnormal root swelling, ethylene overproduction, reduced tolerance to abiotic stresses, and ectopic deposition of lignin in Arabidopsis (Hauser et al, 1995;Schneider et al, 1997;Reed et al, 1998;Cary et al, 2001;Zhong et al, 2002;Rogers et al, 2005;Kwon et al, 2007;Hermans et al, 2010). In addition, cell walls of ctl1/pom1 mutants have an infrared spectrum that closely resembles cellulose-deficient mutants (Mouille et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous screen designed to identify Arabidopsis mutants impaired in the repression of LR elongation by high nitrate concentration, we identified the arm (for anion-related root morphology) mutant that is an allele of CHITINASE-LIKE1 (CTL1; Hermans et al, 2010). Our data showed that the absence of CTL1 modifies root architecture in response to high concentrations of nitrate, chloride, or Suc.…”
mentioning
confidence: 91%
“…Pg_GQ0046_J03.1 further displayed no evidence of a CBD or CTE, and showed a low sequence identity when compared to the other white spruce sequences (Online Resource 7). This sequence showed the most similarity to the A. thaliana sequences encoding CHITINASE-LIKE 1 (CTL1) and CHITINASE-LIKE 2 (CTL2), which are designated class II chitinases, although they lack chitinase activity (Zhang et al 2004;Hermans et al 2010;Sánchez-Rodríguez et al 2012). Both AtCTL1 and AtCTL2 lack the highly conserved histidine-glutamic acid-threonine-threonine (HETT) motif within loop 1 that is essential for chitinase activity (Passarinho and de Vries 2002).…”
Section: Classificationmentioning
confidence: 99%